Handbook of Database Security Applications and Trends - Gertz, Michael; Jajodia, Sushil (Springer US : Imprint: Springer, 2008)
The Handbook of Database Security: Applications & Trends, an edited volume by renowned researchers within data security, provides an up-to-date overview of data security models, techniques, and architectures in a variety of data management applications and settings. This edited volume represents the most comprehensive work on numerous data security aspects published in the last ten years. The Handbook of Database Security: Applications & Trends places a particular focus on data-centric security aspects that reach beyond traditional and well-studied data security aspects in databases. It also covers security in advanced database systems, data privacy and trust management, and data outsourcing, and outlines directions for future research in these fields. The Handbook of Database Security: Applications & Trends is designed for a professional audience composed of practitioners and researchers in industry and academia as a reference book. This volume is also suitable for advanced-level students in computer science interested in the state-of-the-art in data security.